Respuesta :

Answer:

Step-by-step explanation:

As per midsegment theorem of a trapezoid,

Segment joining the midpoints of the legs of the of the trapezoid is parallel to the bases and measure half of their sum.

Length of midsegment = [tex]\frac{1}{2}(b_1+b_2)[/tex]

3). MN = [tex]\frac{1}{2}(18+10)[/tex]

           = 14

4). MN = [tex]\frac{1}{2}(57+76)[/tex]

           = 66.5

5). MN = [tex]\frac{1}{2}(AB+DC)[/tex]

    7 = [tex]\frac{1}{2}(AB+10)[/tex]

    14 = AB + 10

    AB = 14 - 10

    AB = 4

6). 15 = [tex]\frac{1}{2}[(3x+2)+(2x-2)][/tex]

    30 = 5x

     x = 6